Monitoring radioactivity in nuclear and radiological emergency in a European perspective: aims and means. (2nd July 2007) - De Cort, Marc
After the Chernobyl nuclear power plant accident, European countries have further enhanced their capacity and infrastructure for monitoring radioactivity in their environment. This paper gives a summary of the most commonly used techniques relevant to routine and nuclear and/or radiological emergency conditions, followed by a discussion of the various network types (routine, emergency preparedness, mobile monitoring) and some suggestions on how homogeneity of the monitoring information can be improved.